Behavior of four-bolt extended end-plate connection subjected to lateral loading - Elsayed Mashaly; Mohamed El-Heweity; Hamdy Abou-Elfath; Mohamed Osman (Alexandria Engineering Journal, 2011)
A considerable number of literatures have been published on the behavior of end-plate connections in ordinary moment-resisting frames. It was found, experimentally, that this type of connection might act as either a fully-rigid or a semi-rigid connection depending mainly on the thickness of the end plate and the diameter of bolts. In recent years, due to their good ductility and their good ability of energy dissipation, extended end-plate connections are recommended to be widely used in special moment-resisting frames subjected to lateral loads. The purpose of this study is to investigate the effect of both the material and geometric properties of four-bolt extended end-plate connections upon their behavior when subjected to lateral loading. This is done through a parametric study upon a finite element model using the multi-purpose software package ANSYS. The parametric study takes into account 12 parameters which are expected to be effective on the behavior of the studied connection. The results are presented by the relation between the storey drift, which represents the rotation of the connection and the applied lateral load, which simulates the moment on the connection. The results verify that the chosen parameters are considered effective depending on the energy dissipation of the connection.